Jellicoe: a biography - Patterson, A. Temple (Alfred Temple) (London, Macmillan; New York, St. Martin's P., 1969)
"Jump to: navigation, search Admiral of the Fleet The Right Honourable The Earl Jellicoe GCB OM GCVO 2nd Governor-General of New Zealand In office 27 September 1920? 12 December 1924 Monarch George V Preceded by The Earl of Liverpool Succeeded by Sir Charles Fergusson Personal details Born 5 December 1859 Southampton, Hampshire, United Kingdom Died 20 November 1935 (aged 75) London, United Kingdom Military service Allegiance United Kingdom Service/branch Royal Navy Years of service 1872?1919 Rank Admiral of the Fleet Commands HMS Centurion HMS Drake Atlantic Fleet Grand Fleet Battles/wars Egyptian war Boxer Rebellion World War I Battle of Jutland Awards Knight Grand Cross of the Order of the Bath Order of Merit Knight Grand Cross of the Royal Victorian Order Admiral of the Fleet John Rushworth Jellicoe, 1st Earl Jellicoe, GCB, OM, GCVO SGM (5 December 1859? 20 November 1935) was a Royal Navy officer. He fought in the Egyptian war and the Boxer Rebellion and commanded the Grand Fleet at the Battle of Jutland in May 1916 during World War I. His handling of the fleet at that battle was controversial: he made no serious mistakes and the German High Seas Fleet retreated to port? at a time when defeat would have been catastrophic for Britain? but at the time the British public were disappointed that the Royal Navy had not won a victory on the scale of the Battle of Trafalgar. Jellicoe later served as First Sea Lord but was removed at the end of 1917 as a result of his pessimistic view, declaring that nothing could be done to defeat the U-boats. He also served as the Governor-General of New Zealand in the early 1920s."--Wikipedia.
The making of an admiral (1859-1907) -- The coming man (1907-14) -- 'Responsibility is the devil' (1914-15) -- The long haul (1915-16) -- Jutland -- After Jutland (June -- November 1916) -- First Sea Lord (December 1916 -- December 1917) : the submarine peril -- First Sea Lord : dismissal -- The empire mission -- The Jutland controversy and the closing years.
Includes bibliographical references (pages 268-270).
Keywords: Jellicoe, John Rushworth, -- 1859-1935.; Admirals -- Great Britain -- Biography; World War, 1914-1918 -- Naval operations; collective biographies